2022
DOI: 10.1039/d2nj03373a
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism and isomorphism in trans-bis(2,5-diiodopyridine)dihalocopper(ii) complexes: theoretical and crystallographic studies

Abstract: Two polymorphs of each of the complexes, [Cu((25dIpy)2Cl2] and [Cu(25dIpy)2Br2], (where 25dIpy = 2,5-diiodopyridine) have been prepared and characterized by single and powder X-ray diffraction. The two polymorphs of [Cu(25dIpy)2Cl2]...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 70 publications
(104 reference statements)
0
12
0
Order By: Relevance
“…69 Recently, both conformers of Cu(2I5IP) 2 Cl 2 have been characterized, which indicates that the presence of a halogen atom on position 5 of the pyridine will support crystallization of both conformers. 40 The syn-conformer crystallizes from acetonitrile at 60 °C, whereas, both conformers crystallize concomitantly at lower temperatures. Only the anti-conformer crystallizes from 2-propanol.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…69 Recently, both conformers of Cu(2I5IP) 2 Cl 2 have been characterized, which indicates that the presence of a halogen atom on position 5 of the pyridine will support crystallization of both conformers. 40 The syn-conformer crystallizes from acetonitrile at 60 °C, whereas, both conformers crystallize concomitantly at lower temperatures. Only the anti-conformer crystallizes from 2-propanol.…”
Section: Introductionmentioning
confidence: 99%
“…Cu(2ClP) 2 X 2 crystallizes as syn-conformer whereas Cu(2BrP) 2 X 2 and Cu(2IP) 2 X 2 crystallize as anti-conformers. 19,64,67,68 All our attempts to crystallize syn-conformers from either Cu(2BrP) 2 X 2 or Cu(2IP) 2 X 2 have been unsuccessful, 40 even though calculations indicated that the syn-conformer is more stable than the anti-conformer. Cu(2Br5MP) 2 X 2 crystallize as anti-conformers (2Br5MP = 2-bromo-5-methylpyridine).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations